Authentic assessment increased academic achievement and attitude towards the educational measurement of prospective teachers - Ceyhun Ozan (Institute of Advanced Engineering and Science, 2019)
The aim of the study was to investigate the effect of authentic assessment on the attitudes of prospective teachers towards academic achievement and attitudes towards educational measurement and the opinions of prospective teachers on authentic assessment. In this study, the triangulation mixed design was used. In the quantitative dimension of the study, the study group consisted of prospective teachers studying in the education faculty of a state university in the 3rd grade of the Turkish education program of the 2016-2017 fall semesters. All prospective teachers in the experimental group filled in the unstructured diaries from which qualitative data were obtained and 12 of the prospective teachers in the experimental group were selected. Experimental processes were carried out during the 14-weeks assessment and evaluation course. In the experimental group, prospective teachers were given authentic assignments within the scope of the authentic task and alternative assessment practices were conducted. As a result of the study, it was determined that authentic assessment significantly increased the academic achievement and attitude towards the educational measurement of prospective teachers and also it’s an approach that can serve to provide cooperation between the theory and practice which is a major problem in the field of teacher training in Turkey.